Change of Pelvic Sagittal Tilt after Total Hip Arthroplasty in Patients with Bilateral Crowe Type IV Developmental Dysplasia of the Hip. Issue 5 (21st April 2022) - Zhang, Bohan; Du, Yinqiao; Sun, Jingyang; Shen, Junmin; Li, Tiejian; Zhou, Yonggang
Abstract : Objective: To explore and analyze the change of pelvic sagittal tilt (PST) after total hip arthroplasty (THA) in patients with bilateral Crowe type IV developmental dysplasia of the hip (DDH). Methods: The study retrospectively evaluated 43 patients with bilateral Crowe type IV DDH undergoing THA from January 2008 to June 2019 who were followed up for 12 months postoperatively. Four parameters, including the ratio between the height and width of the obturator foramina(H/W ratio), the vertical distance between the upper edge of the symphysis and the middle of the sacrococcygeal joint (SSc distance), the vertical distance between the upper edge of the symphysis and the line connecting bilateral hip centers (SC distance) and the vertical distance between the upper edge of the symphysis and the line connecting the bilateral lower ends of the sacroiliac joints (SSi distance), which could indirectly reflect the change of PST, were observed and measured by radiographs. The change of each parameter before operation, immediately after operation, and in 3, 6 and 12 months postoperatively was compared and analyzed. Results: Compared with the value before operation, the H/W ratio immediately after operation and in 3, 6 and 12 months postoperatively were 0.61 ± 0.12 ( t  = 0.893, P  = 0.377), 0.61 ± 0.11 ( t  = 1.622, P  = 0.112), 0.67 ± 0.10 ( t  = 5.995, P  < 0.001) and 0.76 ± 0.12 ( t  = −9.313, P  < 0.001), respectively, and the SSc, SC and SSi distance in 6 months postoperatively were 30.12 ± 7.06 mm ( t  = 3.506, P  = 0.002), 42.8 ± 7.7 mm ( t  = 5.843, P  < 0.001), 129.3 ± 12.6 mm ( t  = 5.888, P  < 0.001), respectively, and in 12 months postoperatively were 27.24 ± 7.68 mm ( t  = 6.510, P  < 0.001), 36.1 ± 9.1 mm ( t  = 9.230, P  < 0.001), 118.9 ± 14.9 mm ( t  = 8.940, P  < 0.001), respectively. The radiographs obtained in 6 and 12 months postoperatively demonstrated a significantly increased H/W ratio and decreased SSc, SC and SSi distance. At the last follow‐up, the clinical evaluations significantly improved in all patients and there were no revisions. Conclusion: The significant change of pelvic sagittal posterior tilt in patients with bilateral Crowe type IV DDH might be a significant phenomenon after THA, which could occur in 6 months postoperatively. Abstract : We explore the change of pelvic sagittal tilt after total hip arthroplasty in patients with bilateral Crowe type IV developmental dysplasia of the hip. The time and position of significant change in pelvic sagittal tilt could provide guidance for operations.